Evaluation of in vitro antioxidant capacity and reducing potential of polyherbal drug- Bhāraṅgyādi - Kajaria, Divya Kumari (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Present work was designed to investigate antioxidant activity of polyherbal formulation in search for new, safe and inexpensive antioxidant. Clerodendrum serratum, Hedychium spicatum and Inula racemosa, were extensively used in ayurvedic medicine and were investigated together in the form of polyherbal compound (Bhāraṅgyādi) for their antioxidant potential. MATERIALS AND METHODS: Hydroalcoholic extract was prepared from the above samples and was tested for total reducing power and in vitro antioxidant activity by ABTS(+) assay, Superoxide anion scavenging activity assay and lipid per-oxidation assay. RESULT: Reducing power shows dose depended increase in concentration maximum absorption of 0.677 ± 0.017 at 1000 μg/ml compared with standard Quercetin 0.856±0.020. ABTS(+) assay shows maximum inhibition of 64.2 ± 0.86 with EC(50) 675.31 ± 4.24. Superoxide free radical shows maximum scavenging activity of 62.45 ± 1.86 with EC(50) 774.70 ± 5.45. Anti-lipidperoxidation free radicals scavenge maximum absorption of 67.25± 1.89 with EC(50) is 700.08 ± 6.81. Ascorbic acid was used as standard with IC(50) value is 4.6 μg/ml. The result suggests polyherbal formulation to be a good potential for antioxidant activity. Oxidative stress results from imbalance between free radical-generation and radical scavenging systems. This will lead to tissue damage and oxidative stress. CONCLUSION: In conclusion, we strongly suggest that Polyherbal compounds are source of potential antioxidant for radical scavenging. The highly positive correlation of antiradical scavenging activity and total polyphenolic content in Polyherbal compounds indicates that polyphenols are important components which could be used for the free radical scavenging activity. Further study is needed for isolation and characterization of the active moiety responsible for biological activity and to treat in various stress condition.